Pengaruh Gaya Kepemimpinan Transformasional, Lingkungan Kerja Fisik dan Kompensasi Intrinsik terhadap Kinerja Karyawan di CV. Nina Etik Garment Indonesia - Novi Oktavia Fatikhatin; Nersiwad Nersiwad; Kasnowo Kasnowo (Jurnal Visi Manajemen, 2025)
This study aims to determine the influence of transformational leadership style, physical work environment, and intrinsic compensation on employee performance on CV. Nina Etik Garment Indonesia, a written batik industry operating in Mojokerto. The background of this research departs from the phenomenon of low employee productivity which is allegedly influenced by internal and external factors of the organization. The research method used is a quantitative approach with a census method for all permanent employees totaling 39 people. Data analysis was carried out using Structural Equation Modeling–Partial Least Square (SEM-PLS) based on the SmartPLS 4.1.1.2 application. The results show that only the physical work environment has a significant effect on employee performance. This indicates that the factors of comfort, security, and the feasibility of work facilities have a dominant role in improving employee performance. In contrast, transformational leadership styles and intrinsic compensation have not been shown to have a significant impact. These findings provide an idea that the motivation of employees in the creative industry sector based on local culture such as written batik is more influenced by the real working conditions they face on a daily basis than by a leadership approach or non-financial reward alone. The practical implication of this research is the need for company management to prioritize improving the physical aspects of the work environment, such as lighting, ventilation, cleanliness, and ergonomic workspace layout. By creating a comfortable and supportive work environment, employee productivity and performance can be significantly improved. In addition, although there is no significant effect in this study, leadership style and intrinsic compensation still need to be considered in order to create a balance in the sustainable human resource management strategy and be able to support innovation, creativity, and competitiveness of the company.